TATA KELOLA KANDANG DAN PAKAN SERTA IMPLIKASINYA PADA PENGGEMUKAN SAPI Studi pada Desa Sindanglaya Kecamatan Tanjung Siang Kabupaten Subang - Sugiyanto Sugiyanto; Maswarni Maswarni; Nofiar Nofiar; Sachro Yusuf; Juwita Ramadani Fitria (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of community service is to find out how closely the management of the cage and feed does have implications for cattle fattening in the Sindanglaya Village, Subang Regency and the empowerment of the local community. The measurement method uses three approaches including (1) phenomenalogical research method in which the method is based on the philosophy of postpositivism used in object conditions, key instruments, data collection techniques carried out by triangulation (combined) the results of the analysis are inductive to suppress the meaning of Creswell 2009 generalization ( in his book Sugiyono 2017: 24), (2) The grounded theory method of this research is one type of qualitative methods, to attract generalizations that are observed inductively, (3) Ethnography method is qualitative strategy (Crewell 2009) states one type of qualitative research is conducting Study of group culture through interview observation. The results of observations and interviews on community service can be revealed that beef cattle are declared a potential livestock subsector commodity. from the high demand for beef requires effective breakthrough efforts and support from the government and the community. The existence of governance of cows and cattle feed has implications for sustainable cattle fattening programs. The quality of feed is very implicated in the acceleration of beef cattle fattening. The concept of cage management has an impact on cattle health, and traditional food which produces added value in empowering the workforce. for increasing people's welfare.Keywords: Good Corporate Governance, Feed, and Fattening